2020
DOI: 10.3390/foods9081066
|View full text |Cite
|
Sign up to set email alerts
|

New Formulation towards Healthier Meat Products: Juniperus communis L. Essential Oil as Alternative for Sodium Nitrite in Dry Fermented Sausages

Abstract: The effect of Juniperus communis L. essential oil (JEO) addition at concentrations of 0.01, 0.05 and 0.10 µL/g on pH, instrumental parameters of color, lipid oxidation (2-Thiobarbituric acid reactive substances (TBARS)), microbial growth, texture and sensory attributes of dry fermented sausages produced with different levels of fat (15 and 25%) and sodium nitrite (0, 75 and 150 mg/kg) was assessed. Reduced level of sodium nitrite (75 mg/kg) in combination with all three concentrations of JEO (0.01–0.10 µL/g) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 58 publications
(91 reference statements)
15
37
1
Order By: Relevance
“…The samples of DFS were manufactured using lean pork shoulder and pork back fat according to a procedure previously described by Tomović et al [4]. Sodium nitrite (SN) (0, 75 and 150 mg/kg) was added in the DFS batters formulated with two levels of pork back fat (15% and 25%).…”
Section: Preparation Of Dfsmentioning
confidence: 99%
See 3 more Smart Citations
“…The samples of DFS were manufactured using lean pork shoulder and pork back fat according to a procedure previously described by Tomović et al [4]. Sodium nitrite (SN) (0, 75 and 150 mg/kg) was added in the DFS batters formulated with two levels of pork back fat (15% and 25%).…”
Section: Preparation Of Dfsmentioning
confidence: 99%
“…The manufacture of DFS includes the following phases: mincing of the fresh or frozen meat and fat, seasoning and curing, stuffing into casings (natural or collagen), fermenting, smoking and drying, followed by the ripening that provides the typical sensory properties for this type of meat products [2,3]. Due to absence of thermal treatment, relatively high level of fat (15-40%) and usage of diverse raw materials, DFS have a strong risk of microbial growth and lipid oxidation, which consequently reduce the shelf-life of the product and have a significant health hazard to customers [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research results showed a significant antioxidant activity of Juniperus communis L essential oil as an alternative to sodium nitrite in dry fermented sausages [17].…”
Section: Literature Review and Problem Statementmentioning
confidence: 83%